Development of secretory expression system using synthetic signal peptides spA and spD for protein production in Escherichia coli. - Velaithan, Vithya (2011)
ecombinant protein expression is very important in biotechnology. Successful protein expression depends on the expression host, vector and target protein. Escherichia coli being a popular expression host, is still plagued by various problems in expression like formation of inclusion bodies, incorrect folding and low soluble protein yield. These problems can be circumvented by using different promoters, different host strains, co-expression of chaperones, reduction of culture temperature and secretion of proteins into periplasm and culture medium. In this study, periplasmic protein secretion was investigated by using novel synthetic signal peptides, spA and spD. The two signal peptides were designed based on signal peptides of Bacillus spp. for secretion of heterologous proteins. They were amplified and ligated to genes coding for the green fluorescent protein (GFP) and cyclodextrin lucanotransferase (CGTase) to construct secretion cassettes spA*GFP, spD*GFP and spA*CGT and spD*CGT. These secretion cassettes were first cloned into pCR®-Blunt II-TOPO cloning vector. The cassettes were then sub-cloned into pET-32b(+) expression vector to construct pAGFP, pDGFP, pACGT and transformed into competent E. coli BL21(DE3) and BL21(DE3)pLysS cells. The cloning of secretion cassette spD*CGT into pET-32b(+) was not successful. GFP without the signal peptide was cloned into similar pET-32b(+) as a control and the construct was named pGFP. SDS-PAGE and western blotting results for recombinant GFP clones showed successful expression and secretion into the periplasm. Fluorescence analysis for GFP clones showed that the secreted GFP was not fluorescent while cytoplasmically expressed GFP was fluorescent. Induction temperature also affected the secretion of recombinant GFP as better secretion was attained at 37°C. SDS-PAGE analysis for recombinant clone BLpACGT showed that CGTase was detected in both cytoplasm and periplasm but in Western blotting only cytoplasmic expression was detected. However, the positive control, (CGTase with native signal peptide) was detected in both cytoplasm and periplasm. Cell growth analysis for recombinant clones GFP and CGTase did not show any adverse effect to the secretion host. These results show that the synthetic signal peptides, spA and spD, could direct recombinant proteins to the periplasmic space